2006
DOI: 10.1353/hub.2007.0012
|View full text |Cite
|
Sign up to set email alerts
|

Income, Birth Order, Siblings, and Anthropometry

Abstract: The purpose of the present cross-sectional study was to examine the relationship and effect of monthly household income, birth order, and number of siblings on adult body dimensions, adiposity index, and body composition among adult Bengali females. One hundred seventy-one adult Bengali females, age 20.35 +/- 1.51 years (mean +/- SD; range: 18-21 years) from Kolkata (formerly Calcutta) were studied. Anthropometric measures (weight, height, waist circumference, hip circumference, and triceps, biceps, subscapula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
21
1
Order By: Relevance
“…In the present study prevalence of dental caries in permanent dentition demonstrate lower incidences (44.1%) than the finding of Mahejabeen et al, (2006) from southern part of India in preschool children and in corroboration with the study from Eastern India (Mondal et al, 2001) and as well as mean DMFT among the school children of Kerala, India (David et al, 2005). The overall nutritional status in terms of BMI-for age in the present study among the Bengalee School going girls, however, corroborate with earlier studies (Ghosh & Bandyopadhyay, 2006;Ghosh & Bandyopadhyay, 2009) on Bengalee schoolgirls and adults. Examination on prevalence of dental caries in the present study revealed that the underweight group was significantly higher (p < 0.05) than normal and overweight categories.…”
Section: Resultssupporting
confidence: 92%
“…In the present study prevalence of dental caries in permanent dentition demonstrate lower incidences (44.1%) than the finding of Mahejabeen et al, (2006) from southern part of India in preschool children and in corroboration with the study from Eastern India (Mondal et al, 2001) and as well as mean DMFT among the school children of Kerala, India (David et al, 2005). The overall nutritional status in terms of BMI-for age in the present study among the Bengalee School going girls, however, corroborate with earlier studies (Ghosh & Bandyopadhyay, 2006;Ghosh & Bandyopadhyay, 2009) on Bengalee schoolgirls and adults. Examination on prevalence of dental caries in the present study revealed that the underweight group was significantly higher (p < 0.05) than normal and overweight categories.…”
Section: Resultssupporting
confidence: 92%
“…The suggestion that later born children are on average taller than those first born has also been reported elsewhere,33 34 although others have found the inverse to be true 28 35. It may be that issues such as birth spacing and cultural influences on care patterns in families account for these differences, but we did not have the relevant data to explore this issue further.…”
Section: Discussionmentioning
confidence: 52%
“…There seem to be very little data on the association between birth order and height in women, and none from large studies. Previously, the study on Italian women observed no difference in stature between first-borns and later-borns,10 while among Indian women, there was a weak correlation between birth order and stature (r=−0.20), but the magnitude of the effect was not quantified 11. In contrast, data from large studies have consistently reported differences in men.…”
Section: Discussionmentioning
confidence: 90%
“…In Italy, among 383 overweight or obese women, first-borns had more body fat and had BMI that was 4 kg/m 2 greater than later-borns 10. Similarly, a study on 171 young adult women in India showed that birth order was negatively correlated with BMI and fat mass 11. Among 1458 teenage girls in Poland, there was no difference in BMI SDS between first-borns and second-borns, but first-born girls were 1.5 times more likely to be obese than later-borns 12…”
Section: Discussionmentioning
confidence: 99%